A model to understand type I oxidations of biomolecules photosensitized by pterins - Lorente, Carolina (2021)
Photosensitized oxidations, in part responsible for the harmful effect of UV and visible radiation on biological systems, can take place through type I (generation of radicals) and type II (singlet oxygen) mechanisms. Pterins are heterocyclic compounds, widespread in living systems and involved in relevant biological functions. Pterins present a profuse and amazing photochemistry and are endogenous photosensitizers that act mainly via type I mechanism. This survey is aimed to contribute to a better understanding on the complex set of competitive pathways involved in type I photosensitization. Based on studies performed in model systems with pterins as photosensitizers, this review explores the mechanisms involved in the type I photooxidations of proteins, DNA and lipids sensitized by pterins. The generation of radicals and their subsequent reactions are described together with the analysis of the role of O 2 and reactive oxygen species. The chemical modification of pterins seeking for better properties and the effect of the photochemical processes at a cellular level are also analyzed.